Taste and Smell Disorders in COVID-19 Patients at a Local Healthcare Trust in Northern Italy: a CrossSectional Study - Piu, N.; Isabella, A.; Airoldi, C.; Aleni, C.; Sarro, A.; Faggiano, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. In Italy, since the beginning of the COVID-19 pandemic, patients testing positive for SARSCoV-2 through nasopharyngeal swab have reported taste and smell alterations. As these symptoms are quite uncommon in other respiratory infections, their specificity and prevalence are useful features for the differential diagnosis of COVID-19. The objective was to describe taste and smell alterations in patients diagnosed with SARS-CoV-2 infection and to define the onset of those disorders during the clinical course of the disease. Study design. Cross-sectional study. Methods. This study was conducted on adult patients testing positive for SARS-CoV-2 infection through nasopharyngeal swab at a Local Healthcare Trust in Northern Italy between April 27th and May 27th, 2020. In order to investigate the clinical course, the onset of the first symptoms, smell and/or taste alterations, a phonebased questionnaire was administered during the programming of the second nasopharyngeal swab. Results. We recruited 168 patients; the mean age was 52 years old, and 94 (56.0%) were female. Among the 135 symptomatic patients, 87 (64.4%) reported taste and smell alterations. Patients with a mild clinical course showed the highest prevalence for taste and smell disorders (76.6%), which were also associated with a more benign clinical course of the disease (P = 0.0166). Furthermore, in 33 (37.9%) of these patients, changes in smell and taste perception appeared before the acute phase of the disease. Among the 14 patients with a severe clinical course of SARS-CoV-2 infection, 8 reported a variation of taste and smell perception before the hospitalization, with a median of 4 days (IQR 2-7) Conclusions. Smell and taste disorders can be listed among the first symptoms of SARS-CoV-2 infection and may anticipate the acute phase of the disease. Noteworthy, they seem to be associated with a more benign clinical course.